Deltaproteobacterium Strain KaireiS1, a Mesophilic, Hydrogen-Oxidizing and Sulfate-Reducing Bacterium From an Inactive Deep-Sea Hydrothermal Chimney - Adam, Nicole; Han, Yuchen; Laufer-Meiser, Katja; Bährle, Rebecca; Schwarz-Schampera, Ulrich; Schippers, Axel; Perner, Mirjam (Frontiers in Microbiology, 2021)
A novel deltaproteobacterial, mesophilic, hydrogen-oxidizing and sulfate-reducing bacterium (strain KaireS1) was highly enriched from an inactive chimney located in the active zone of the Kairei hydrothermal vent field (Central Indian Ridge) in the Indian Ocean. Based on 16S rRNA gene analyses, strain KaireiS1 is the currently only cultured representative of a cluster of uncultured Deltaproteobacteria, positioned within the Desulfobulbaceae family, between the Desulfobulbus genus and the “Cable Bacteria”. A facultative autotrophic lifestyle of KaireiS1 is indicated by its growth in the absence of organic compounds, measurements of CO2-fixation rates and activity measurements of carbon monoxide dehydrogenase, the key enzyme of the reductive Acetyl-CoA pathway. Apart from hydrogen, strain KaireiS1 can also use propionate, lactate and pentadecane as electron donors. However, the highest cell numbers were reached when grown autotrophically with molecular hydrogen. Hydrogen uptake activity was found in membrane and soluble fractions of cell-free extracts and reached up to 2981 ± 129 nmol H2*min-1*mg-1 of partially purified protein. Commonly, autotrophic sulfate-reducing bacteria from the Deltaproteobacteria class, thriving in hydrothermal vent habitats are described as thermophiles. Given its physiological characteristics and specific isolation source, strain KaireiS1 demonstrates a previously unnoticed potential for microbial sulfate reduction by autotrophs taking place at moderate temperatures in hydrothermal vent fields.